THE PLACE AND ROLE OF SOCIOLOGICAL RESEARCH IN PROTECTING THE HEALTH OF CITIZENS OF THE RUSSIAN FEDERATION - Кожевников, Андрей Александрович; Данцигер, Дмитрий Григорьевич; Филимонов, Сергей Николаевич; Часовников, Константин Викторович; Херасков, Виталий Юрьевич (Medicine in Kuzbass, 2025)
The article evaluates the need for information on the nature of relations between federal, regional authorities and the local community on the issue of protecting the health of the population living in particularly harsh (extreme) living and working conditions. At the same time, the existing developments in ensuring public health protection in the context of the sociological component require serious scientific substantiation.
Keywords: public health and public health; public health protection; sociological research